Proceedings of the Annual Symposium on Computer-Human Interaction in Play 2020
DOI: 10.1145/3410404.3414229
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Significance Testing at CHI PLAY: Challenges and Opportunities for More Transparency

Abstract: Statistical Signifcance Testing -or Null Hypothesis Signifcance Testing (NHST) -is common to quantitative CHI PLAY research. Drawing from recent work in HCI and psychology promoting transparent statistics and the reduction of questionable research practices, we systematically review the reporting quality of 119 CHI PLAY papers using NHST (data and analysis plan at OSF.io). We fnd that over half of these papers employ NHST without specifc statistical hypotheses or research questions, which may risk the prolifer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 134 publications
(183 reference statements)
1
25
0
Order By: Relevance
“…In line with Vornhagen et al [53] we discuss why precisely defining a construct before its measurement is necessary for interpretable and generalizable findings. Referencing DeVellis [18] conceptualization of content validity, researchers cannot be certain that the content, or items, of a scale is appropriate for their chosen construct if they do not have a clear definition of their construct.…”
Section: Defining Constructssupporting
confidence: 58%
See 1 more Smart Citation
“…In line with Vornhagen et al [53] we discuss why precisely defining a construct before its measurement is necessary for interpretable and generalizable findings. Referencing DeVellis [18] conceptualization of content validity, researchers cannot be certain that the content, or items, of a scale is appropriate for their chosen construct if they do not have a clear definition of their construct.…”
Section: Defining Constructssupporting
confidence: 58%
“…As explained above, the constructs we measure and the measurement we chose for these constructs are a fundamental challenge of every empirical study. In their paper Vornhagen et al [53] gave a broad idea as to how theoretical variables should be reported in studies. They explain these constructs must be precisely defined, the measurement procedure must be elaborated on and the selection of measurements must be justified.…”
Section: General Concerns When Reporting Measurementsmentioning
confidence: 99%
“…We surveyed 237 boardgame players about their attitudes towards and experience with HDBs. This was explicitly exploratory research [121,132]; we wanted to see what people would tell us about HDBs, given the opportunity. Respondents were recruited via the project's and researchers' social media accounts, as well as at international gaming events, trade fairs and conventions in Europe, the US, and Australia, as well as through posts on hobbyist gaming websites.…”
Section: Surveymentioning
confidence: 99%
“…This finding, however, is not entirely surprising, not only because of the different disciplines involved but also because some of the contributing research areas struggle with similar challenges themselves. For instance, Human-Computer-Interaction research that investigates video games often encounters substantial methodological and statistical challenges (Vornhagen et al, 2020), whereas educational psychology faces related issues, such as the replication crisis (Maxwell et al, 2015) or infrequent improvements to theoretical frameworks (Alexander, 2018;Mayer, 2018). Nonetheless, the results of this review can be used to address these critical issues and improve future empirical research in the field.…”
Section: Overall Conclusionmentioning
confidence: 99%